SOCIAL NETWORKING IN PRAGUE UNIVERSITY OF ECONOMICS AND BUSINESS - Arunachalam, Santhosh Narayanan; Pavlíček, Antonín, 1977-; Böhmová, Lucie; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
Social Network Analysis (SNA) is a valuable tool for analyzing these networks, enabling the efficient use of resources, and supporting knowledge creation. This thesis explores the current gaps and innovative approaches for managing the university’s social media presence in social media platforms. The objective is to unify the platform to enhance knowledge management within the university’s systems. As universities turn to social media for digital communication, engagement, and partnership, it becomes crucial to understand the dynamics of these networks to manage them effectively. SNA offers insights into user interaction patterns within these networks, providing valuable information for knowledge creation, communication, and community growth. By uncovering hidden communities and identifying key influencers, SNA facilitates knowledge sharing. The findings seek to advance Knowledge Management by promoting a data-informed approach to university marketing, focusing on the use of SNA for social media management, internal communication enhancement, and academic collaboration support. This research highlights existing gaps in knowledge management practices, particularly the challenges universities face in maintaining long-term engagement and collaboration within online communities. SNA insights can help universities optimize their marketing strategies, reinforce their digital presence, and build meaningful connections with students. As a result, this research will provide recommendations for refining content strategies, reaching target audiences more effectively, and leveraging social media for institutional growth.
Vedoucí práce: Antonín Pavlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses